STUDY REGARDING THE POSSIBILITIES TO USE THE APPLICATION PRODENT IN THE PRO-PROSTHETIC STAGE - Doriana Forna; Feier Ramona; Topoliceanu Claudiu; Norina Forna; Popescu Eugenia (Romanian Society of Oral Rehabilitation, 2017)
The study aimed to investigate the possibilities to use the system expert Prodent (Neotech) in the planning of the pre-implant and implant therapy. Materials and method. The study groups included 40 patients that were programmed for implant therapy in the Clinical Base "Kogalniceanu M" of Dental Faculty, U.M.F."Gr.T.Popa" Iasi. The computerized planning and the measurement of clinical-biological indices were performed using PRODENT Acad Expert (used for the data recording and creation of database) and PRODENT Indici (Neo-Tech, România). Results. The mean value of clinical-biological indices increases from 0,64 (primary assessment) to 0,69 (secondary assessment). Following the data processing of the patients in study group, there is an increase of the values from each category of the clinical-biological indices. For the selected patients, PRODENT Indici recommends the prosthetic therapy supported by implants with maximal value (1), superior to metal-based removable partial denture (0,38), or acrylic removable prosthesis (0,13) Conclusions. The application Prodent is useful to optimize the treatment plan, to select the best prosthetic therapeutic solutions, and to make prognosis on long term, by analysis of various clinical-biological indices and scores of therapeutic solutions